The Existence of an arak-arakan Tradition as a Heritage of Local Cultural Values (Ethnographic Study of the Community of Cipaat Village, Indramayu Regency) - Fahmi, Muhammad Rijal (International Journal Pedagogy of Social Studies, 2020)
This research is motivated because the researcher is interested in the existence of the arak-arakan tradition as the inheritance of local cultural values in the people of Cipaat Village, Indramayu Regency. In this study, researchers used a qualitative approach to the study of ethnography. These findings indicate that (a) the history of the formation of a arak-arakan tradition originated from the Subang area and experienced development in 1980 in the surrounding area namely Indramayu. (b) The procession of arak-arakan tradition is carried out into 3 stages, namely the opening which begins with a background dance, the stage of core that surrounds the village, and the closing stage which is characterized by magic/drama show. (c) the social relations contained in the arak-arakan tradition are to uphold friendship and harmony in kinship. (d) Efforts to maintain the existence of a arak-arakan tradition are always to keep abreast of the times and pay attention to the quality of tools and equipment. and (e) Inheritance of local cultural values contained in the arak-arakan tradition is religious values, social values and moral values that can be implemented in daily life activities.Keywords : Arak-arakan, Exsistence, Â Heritage of Local Cultural Values.